Crystal structure of myotoxin II, a monomeric Lys49-phospholipase A2 homologue isolated from the venom of Cerrophidion (Bothrops) godmani - Arni, Raghuvir K. (1999)
Lys49-Phospholipase A2 (Lys49-PLA2) homologues damage membranes by a Ca2+-independent mechanism which does not involve catalytic activity. With the aim of determining the structural basis for this novel activity, we have solved the crystal structure of myotoxin-II, a Lys49-PLA2 isolated from the venom of Cerrophidion (Bothrops) godmani (godMT-II) at 2.8 A resolution by molecular replacement. The final model has been refined to a final crystallografic residual (Rfactor) of 18.8% (Rfree = 28.2%), with excellent stereochemistry. godMT-II is also monomeric in the crystalline state, and small-angle X-ray scattering results demonstrate that the protein is monomeric in solution under fisicochemical conditions similar to those used in the crystallographic studies.